Non-realistic elements in the Russia / “collective West” conflict - Sunami, Artem (Sociološki pregled, 2023)
The article examines the Russia / ”Collective West” conflict since Vladimir Putin’s Munich speech at 2007 to last Ukrainian crisis. Using classic conflict theories expounded by L. Coser, R. Dahrendorf, K. Boulding, L. Kriesberg, the author analyzes the tendency of the gradual prevalence of the conflict of values over the conflict of interests in Russia/“Collective West” relations. It opines that the irrationalization of the conflict makes non-realistic improvements to conflict that loses its previous ontological features, attachment to a geographical, cultural or political location, and the goals that it manifests acquire an existential character. The author concludes that only the return of the conflict to the basic state of the conflict of interests is able to connect peace initiatives with the real interests of all parties again.